2016
DOI: 10.1007/s10865-016-9788-9
|View full text |Cite
|
Sign up to set email alerts
|

Replacing sedentary time with sleep, light, or moderate-to-vigorous physical activity: effects on self-regulation and executive functioning

Abstract: Introduction Recent attention has highlighted the importance of reducing sedentary time for maintaining health and quality of life. However, it is unclear how changing sedentary behavior may influence executive functions and self-regulatory strategy use, which are vital for the long-term maintenance of a health behavior regimen. The purpose of this cross-sectional study is to examine the estimated self-regulatory and executive functioning effects of substituting 30 minutes of sedentary behavior with 30 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 79 publications
(88 reference statements)
1
105
4
4
Order By: Relevance
“…When scored with an interruption period of 60 min, those with at least 10 h of wear time on at least 3 days were retained in analyses (Troiano et al, 2008; Peterson et al, 2010). These data were downloaded as activity counts, which represent raw accelerations that have been summed over a specific epoch length (e.g., 60 s), and these counts vary based on frequency and intensity of the recorded acceleration (Fanning et al, 2016). Next, these data were processed using cut points designed specifically for older adults (Copeland and Esliger, 2009) such that 50 or fewer counts per minute corresponded with sedentary behavior, 51–1,040 counts per minute corresponded to light PA, and 1,041 counts or greater represented moderate-to-vigorous PA (MVPA), related to increased heart rate and ventilation (Rejeski et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…When scored with an interruption period of 60 min, those with at least 10 h of wear time on at least 3 days were retained in analyses (Troiano et al, 2008; Peterson et al, 2010). These data were downloaded as activity counts, which represent raw accelerations that have been summed over a specific epoch length (e.g., 60 s), and these counts vary based on frequency and intensity of the recorded acceleration (Fanning et al, 2016). Next, these data were processed using cut points designed specifically for older adults (Copeland and Esliger, 2009) such that 50 or fewer counts per minute corresponded with sedentary behavior, 51–1,040 counts per minute corresponded to light PA, and 1,041 counts or greater represented moderate-to-vigorous PA (MVPA), related to increased heart rate and ventilation (Rejeski et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…One study showed that children who replaced sedentary time with MVPA scored better on tests of self-regulation (Fanning et al, 2017).…”
Section: Physical Activity and Executive Functionmentioning
confidence: 99%
“…These studies also showed benefits that extended to the cognitive domain. One study showed that children who replaced sedentary time with MVPA scored better on tests of self‐regulation (Fanning et al, ). Another study with preschool children suggested that decreasing light physical activity and increasing vigorous physical activity may be beneficial for cognitive and psychosocial development (McNeill, Howard, Vella, Santos, & Cliff, ).…”
Section: Introductionmentioning
confidence: 99%
“…To explore the theoretical effect of substituting time in one behavior with another, isotemporal substitution method has been developed and applied frequently in the field of physical activity research last years. [20][21][22] For instance, utilizing isotemporal substitution models we showed that substituting sedentary time with MVPA is associated with reduced cardiovascular disease mortality. 23 Other reports have shown that substituting time in LIPA with MVPA is associated with more favorable waist circumference or HDL cholesterol 21 and substituting SB with standing or stepping activity is associated with improved cardio-metabolic health.…”
mentioning
confidence: 99%